Tinjauan Yuridis Perlindungan Konsumen Terhadap Produk Mutiara Imitasi - Haerul Kurniawan; H. Djumardin Djumardin (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the implementation and responsibility of buying and selling imitation pearls at UD Ocin Pearl to- the consumer. This research applies empirical legal research methods using facts that occur in the field, and normative legal methods, namely legal research that defines law as a building system of norms such as legislation and various data. The implementation of this imitation pearl sale and purchase agreement is carried out by small traders who take the imitation pearl at the UD Store. Ocin. This imitation pearl was then traded in front of the hotel visited by out-of-town and local guests at an affordable price.